Analysis Cooperative Conventional in Push Sustainability Economypublic - Nurhafifi; Karina Utami Anastuti (Universitas Islam Malang, 2024)
Cooperatives as one of the pillars of the people's economy have an important role in encouraging the sustainability of the community's economy. This research aims to analyze the role of the Pakis Village Unit Cooperative (KUD) in encouraging the economic sustainability of the community in the area where it operates. This research uses qualitative methods with case studies. Data was collected through library research and using internet searching. The research results shows that KUD Fern is proven to be capable to encourage the economics sustainability of the community in its operations areas.